2012
DOI: 10.1016/j.cub.2012.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Planar Polarity Specification through Asymmetric Subcellular Localization of Fat and Dachsous

Abstract: SummaryTwo pathways regulate planar polarity: the core proteins and the Fat-Dachsous-Four-jointed (Ft-Ds-Fj) system. Morphogens specify complementary expression patterns of Ds and Fj that potentially act as polarizing cues. It has been suggested that Ft-Ds-Fj-mediated cues are weak and that the core proteins amplify them [1, 2]. Another view is that the two pathways act independently to generate and propagate polarity [3, 4]: if correct, this raises the question of how gradients of Ft and Ds expression or acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
279
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(320 citation statements)
references
References 29 publications
(31 reference statements)
21
279
1
3
Order By: Relevance
“…More observations will be needed to dissect the mechanism by which Dachs polarizes growth radially in the wing pouch. Brittle et al observed a cellular-level polarity of Dachs near the hinge region at very late stages of larval development (Brittle et al, 2012). Although we find that Dachs is not polarized at earlier stages and that it is not required for cell stretching (Fig.…”
Section: The Origin Of Mechanical Stresscontrasting
confidence: 51%
“…More observations will be needed to dissect the mechanism by which Dachs polarizes growth radially in the wing pouch. Brittle et al observed a cellular-level polarity of Dachs near the hinge region at very late stages of larval development (Brittle et al, 2012). Although we find that Dachs is not polarized at earlier stages and that it is not required for cell stretching (Fig.…”
Section: The Origin Of Mechanical Stresscontrasting
confidence: 51%
“…Cells in the eye become polarised through preferential distribution of the cadherin Ds (A*) to one cell end and its binding partner the cadherin Ft (B*) to the opposite cell end (Ambegaonkar et al, 2012;Brittle et al, 2012). Planar polarity patterns are specified by opposite gradients in expression of Ds and the Golgi-associated protein Four-jointed (Fj) (Simon, 2004).…”
Section: Hypothesismentioning
confidence: 99%
“…Data from cell culture studies and from overexpression and mutant clones suggest that Ft and Ds form trans-heterodimers (Ma et al, 2003;Matakatsu and Blair, 2004;Strutt and Strutt, 2002). Ft and Ds can also localize on opposite sides of a cell, along the polarity axis ( Figure 3E) (Ambegaonkar et al, 2012;Brittle et al, 2012). Unlike classical cadherins, there is no evidence of homodimers of either Ft or Ds forming across cells (Brasch et al, 2012;Matakatsu and Blair, 2004).…”
Section: Introduction To Pcpmentioning
confidence: 99%
“…PCP is also evident in dynamic processes, such as oriented cell division in Drosophila imaginal discs (Baena-Lopez et al, 2005) and cell intercalation during zebrafish neurulation (Ciruna et al, 2006). Ft and Ds cadherins act together with Fj, D, and the transcriptional co-repressor Atrophin (Atro) to regulate PCP (Thomas and Strutt, 2012). Vertebrate orthologs of Drosophila ft and ds, such as fat1, fat4, and dachsous1 also regulate PCP (Mao et al, 2011a;Saburi et al, 2008;Saburi et al, 2012).…”
Section: Introduction To Pcpmentioning
confidence: 99%
See 1 more Smart Citation